(untitled) (Carte Romanze, 2020)
A great European success, the Dialogus creaturarum (14th century) was translated twice into French in 1482; yet, the two translators reacted differently to the Latin proverbial couplets which mark the passage in each Dialogue from the fable to its moralization. A comparative analysis of the translators’ work on the couplets can contribute to a definition of what a «proverb» was in Middle French.